CO2 Emissions Decoupling from Added Value Growth in the Chemical and Pharmaceutical (CHPH) Industry in Nigeria - Abam, Fidelis Ibiang; Inah, Oliver Ibor; Ekwe, Ekwe B.; Igbong, Dodeye I.; Effiom, Samuel O.; Ovat, Friday A.; Nyong, Oku E.; Ikem, Ikem A. (Green and Low-Carbon Economy, 2023)
Nigeria's in its Third National Communication (NTNC) current emissions estimate stipulate that its emissions intensities will continuously increase till 2030, and mitigations measures may not be deep and adequate to meet the upper range of its national reduction goals. Analysing the decoupling states with industrial added-value (IAV) growth, carbon emissions (CE) and the driving forces from a firm-level perspective is critical for the Nigerian state to actualised its 2030 emission reduction objective. Based on the Logarithm Mean Divisia Index (LMDI) procedure and the Tapio index approach, the drivers of CE in Nigeria's chemical and pharmaceutical (CHPH) industry were decomposed, and the decoupling states were measured between 2000 and 2020. The results show that CE increased from 4228.3 Mt in 2000 to 22220.7 Mt in 2020, an approximately 4.3% increase. The IAV growth in this period increased by 1.667%, while the coefficient of emission contracted in 2009 with an average progression rate of 4.4%. The decomposition analysis shows that the most influencing factors of CE were the change in the energy mix (∆EMIX) and energy intensity (∆EI) effects. In contrast, the carbon emissions coefficient (∆CI) effect was the significant driver that reduced CO2 emission. Two decoupling states were revealed: expansive negative decoupling (END) and strong negative decoupling (SND). Conversely, overall, the CE of Nigeria's CHPH industry demonstrated an expansive negative decoupling state with IAV growth. This suggests that the industry's energy consumption increased faster than value-added, with the resultant effect of emissions on the environment. However, the study made clear recommendations for low-carbon policy and environmental sustainability. Received: 1 January 2023 | Revised: 9 February 2023 | Accepted: 15 February 2023 Conflicts of Interest The authors declare that they have no conflicts of interest to this work.